1996
DOI: 10.1016/0014-5793(96)00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine analogues stimulate DNA synthesis by a mechanism not involving phosphatidylethanolamine synthesis

Abstract: Dimethylethanolamine (0.5-1 mM), added to serumstarved N1H 3T3 fibroblasts, stimulated DNA synthesis 11-32-fold, and it also greatly enhanced the relatively modest (15-20-fold) mitogenic effect of insulin. Ethanolamine and momomethylethanolamine alone had no effects on DNA synthesis, but they also enhanced the stimulatory effect of insulin, although less effectively than dimethylethanolamine did. Lower concentrations (2.5-5 ~tglml) of compound D 609 (tricyclo-9-yl-xanthogenate), which had no effects on phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Ethanolamine (10), and particularly its methylated analogues (11,12), can greatly enhance insulin-induced DNA synthesis by a wortmannin-sensitive mechanism not involving PtdEtn synthesis. PMA also potentiates the mitogenic effect of insulin by a wortmannin-sensitive mechanism (9).…”
mentioning
confidence: 99%
“…Ethanolamine (10), and particularly its methylated analogues (11,12), can greatly enhance insulin-induced DNA synthesis by a wortmannin-sensitive mechanism not involving PtdEtn synthesis. PMA also potentiates the mitogenic effect of insulin by a wortmannin-sensitive mechanism (9).…”
mentioning
confidence: 99%
“…ethanolamines [28,29]. Considering that serum levels of Etn in 50 µM [30] (and references therein), the effects of Etn we ob-served on insulin-induced mitogenesis would require greatly ele-(ϩ1651)3′.…”
mentioning
confidence: 99%
“…Similarly, DEA protected hematopoietic progenitor cells and murine L1210 leukemia cells from cytotoxicity of the chemotherapeutic agent mechlorethamine (28). Moreover, DEA promoted DNA synthesis of NIH-3T3 fibroblast cells in serum-free conditions, and both DEA and MEA enhanced insulin-induced DNA synthesis (29). However, it should be noted that, in these studies, the effects of MEA and DEA were examined at very high concentrations (at the mM range) and in different cell types.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have demonstrated protection against apoptosis by the methylated EA analogues MEA and DEA (27)(28)(29). Therefore, we examined the effect of these methyl derivatives of EA on low serum-induced apoptosis.…”
Section: Metabolism Of Aea To Ethanolamine Is a Criticalmentioning
confidence: 99%